2013
DOI: 10.1109/tse.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Features to Improve Code Change-Based Bug Prediction

Abstract: Abstract-Machine learning classifiers have recently emerged as a way to predict the introduction of bugs in changes made to source code files. The classifier is first trained on software history, and then used to predict if an impending change causes a bug. Drawbacks of existing classifier-based bug prediction techniques are insufficient performance for practical use and slow prediction times due to a large number of machine learned features. This paper investigates multiple feature selection techniques that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
130
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(133 citation statements)
references
References 46 publications
(59 reference statements)
2
130
0
1
Order By: Relevance
“…Song et al [3] pointed out that feature selection is an indispensable part of a general defect prediction framework. Shivaji et al [9] investigate the impact of six methods on the classification-based bug prediction. They found that selecting about 10% features could achieve a satisfactory performance.…”
Section: A Feature Selection On Sddmentioning
confidence: 99%
“…Song et al [3] pointed out that feature selection is an indispensable part of a general defect prediction framework. Shivaji et al [9] investigate the impact of six methods on the classification-based bug prediction. They found that selecting about 10% features could achieve a satisfactory performance.…”
Section: A Feature Selection On Sddmentioning
confidence: 99%
“…The four well-performed algorithms are chosen in text data [13,19] and software data, namely Information Gain (IG), χ2 statistic (CH) [14], Symmetrical Uncertainty attribute evaluation (SU), and Relief-F Attribute selection (RF). The chi-squared distribution also known as chi-square or χ² distribution with k degrees of freedom is the distribution of a sum of the squares of k independent criterion normal random variables.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Shivaji and colleagues [14] proposed the feature selection techniques to predict the software bugs. Fu.Y, Zhu.X, and Li.B [7] investigated to obtain the accurate prediction model with minimum cost by labelling most informative instances.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the data quality, Khoshgoftaar et al [11] and Gao et al [7] inspect the methods on feature selection to manage imbalanced defect records. Shivaji et al [23] suggests a structure to inspect multiple feature selection algorithms and eliminate noise features in classification-based defect prediction. Besides feature selection in defect prediction, Kim et al [13] present how to measure the noise confrontation in defect prediction and how to perceive noise data.…”
Section: ) Data Quality In Defect Predictionmentioning
confidence: 99%